1980
DOI: 10.1113/jphysiol.1980.sp013412
|View full text |Cite
|
Sign up to set email alerts
|

Search for a cardiac nociceptor: stimulation by bradykinin of sympathetic afferent nerve endings in the heart of the cat.

Abstract: SUMMARY1. We have examined the effect of bradykinin on impulse traffic in sympathetic afferent fibres from the heart, great vessels and pleura, and have attempted to identify cardiac nociceptors that on the basis of their functional characteristics might have a role in the initiation of cardiac pain.2. In anaesthetized cats, we recorded afferent impulses from 'single-fibre' slips of the left 2nd-5th thoracic rami communicantes and associated chain, and selected fibres arising from endings in the heart, great v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
107
0

Year Published

1985
1985
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 220 publications
(109 citation statements)
references
References 20 publications
2
107
0
Order By: Relevance
“…There is conflicting literature about adenosine action on cardiac afferents, with some groups supporting a role in cardiac pain (37)(38)(39) and others not (40,41). Bradykinin increases firing of cardiac afferents in vivo (40,42) by acting at B 2 receptors (43). It is cleaved from kininogens by the enzyme kallikrein, which can be triggered by a drop in pH.…”
Section: Resultsmentioning
confidence: 99%
“…There is conflicting literature about adenosine action on cardiac afferents, with some groups supporting a role in cardiac pain (37)(38)(39) and others not (40,41). Bradykinin increases firing of cardiac afferents in vivo (40,42) by acting at B 2 receptors (43). It is cleaved from kininogens by the enzyme kallikrein, which can be triggered by a drop in pH.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, it is possible to deliver a high concentration of stimulants to pulmonary afferents without directly entering the circulation. In several respects, the use of local injection to study reflexes from pulmonary afferents is similar to topical application of stimulants in studying other organs, such as the heart (3,20) and abdominal-visceral organs (8). The concentration of bradykinin used in the present study is comparable to that reported in the topical application to the heart [from 1 g/ml (3,20) to 10-100 g/ml (30)] and to the gut [10 g/ml (8)].…”
Section: Discussionmentioning
confidence: 99%
“…Because the injections were into the most peripheral lung, no obvious blood vessels were encountered. Bradykinin produces tachyphylaxis in cardiac receptors (3); therefore, at least 15 min elapsed between injections. To further determine whether the observed responses were related to activation of pulmonary afferents, rather than originating from the systemic vasculature, in separate trials in six rabbits we compared the hypotensive effects of acetylcholine (0.1 ml of 10 Ϫ4 M) when it was directly injected into the lung and into the right atrium.…”
Section: Methodsmentioning
confidence: 99%
“…Thus, a possible contribution of chemical substances released by coronary occlusion to excite the cardiac afferents cannot be excluded from the present study. Previous studies also suggested that the sympathetic afferent nerves may transmit the sensation of pain during myocardial ischemia to the central nervous system (WHITE, 1957;BAKER et a!.,1980;BLAIR et a!., 1982). Thus, further experiments are required to evaluate the net autonomic response to cardiogenic hypotension determining the central interactions of input from cardiac sympathetic afferents and from arterial baroreceptors and cardiac vagal afferents, and to determine more exact interaction with impaired cardiac function and cardiac sympathetic afferents during the hypotension induced by coronary occlusion.…”
Section: Discussionmentioning
confidence: 99%
“…However, the nature of the stimulus to cardiac receptors was not investigated in the present study. The efferent sympathetic excitatory responses to coronary occlusion may have been initiated by chemical NEURAL RESPONSE TO CARDIAC ISCHEMIA 521 substances such as bradykinin or potassium (REIMANN and WEAVER, 1980;BAKER et al, 1980), as well as mechanical stimuli to the heart. Thus, a possible contribution of chemical substances released by coronary occlusion to excite the cardiac afferents cannot be excluded from the present study.…”
Section: Discussionmentioning
confidence: 99%